Characterisation of the microorganisms and determination of the chemical constituents of Marula brews during fermentation - Maluleke, Evelyn (My University, 2019)
Marula wine plays a fundamental role in the livelihoods of rural communities where it enhances social cohesion and also provides a reasonable income to the primary traders who often have no alternative source of income. Spontaneous fermentation will inevitably include microbes that produce undesirable metabolites, which lead to the spoilage and short shelf life of the wine. The aim of this study was to profile the microbial and chemical changes during fermentation of marula wine. Marula wines were collected from three areas in the Limpopo province namely: University of Limpopo, The Oaks village and Makhushane village. The bacterial species Gluconobacter oxydans, Acetobacter pasteurianus, Lactobacillus brevis, Lactobacillus nagelii, Lactobacillus parabuchneri and Lactobacillus plantarum species and yeast species Hanseniaspora guilliermondii, Pichia guilliermondii, Saccharomyces cerevisiae, Rhodotorula mucilaginosa and Meyerozyma caribbica were identified in marula wines at varying stages of fermentation. Non-fermenting yeast species such as H. guilliermondii together with lactic acid bacteria such as L. brevis and L. plantarum and the Enterobacteriaceae dominated the early stages of fermentation, whereas S. cerevisiae and Acetic acid bacteria dominated the late stages of fermentation. Chemical profiling of the marula juice and wine, which was achieved using both high performance liquid chromatography (HPLC) and gas chromatography (GC), revealed sucrose as the most abundant sugar in the marula juice with a range of 60.43 mg/mL to 73.20 mg/mL. Volatile organic compounds such as ethanol, ethyl acetate and isobutanol were observed during the fermentation process with none to very little of the volatile compounds detected in marula juice. Ethyl-acetate was the most abundant compound whereas ethanol concentration was observed to be high during the late stages of fermentation at a range of 1.16 g/L to 12.63 g/L. Common microbiota from different marula wines showed low intraspecific diversity indicating that the microorganisms responsible for the spontaneous fermentation are the same throughout the different areas that were selected for this study. The outcomes of the study provide empirical data to develop a wine with a long shelf life.
Thesis (M. Sc. (Microbiology) -- University of Limpopo, 2019
Keywords: Marula wine; Social cohesion; Income generation; Fermentation; Yeast